1985
DOI: 10.1111/j.1432-1033.1985.tb09006.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic carbamoyl phosphate metabolism

Abstract: 1. The interrelationship between the two carbamoyl phosphate pools in intact hepatocytes and intact liver was studied with respect to de novo pyrimidine synthesis by use of selective inhibitors of the mitochondrial and the cytosolic carbamoyl-phosphate synthetase.2. Inhibition of mitochondrial carbamoyl phosphate synthesis by 4-pentenoate was without effect on galactosamine-stimulated pyrimidine synthesis. Conditions favouring mitochondrial carbamoyl phosphate accumulation, like excess ammonium ions or L-norva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
16
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
(13 reference statements)
4
16
0
Order By: Relevance
“…CPS1 plays a crucial role in removing excessive ammonia by converting ammonium into carbamoyl phosphate in the liver (16), which is a de novo resource of arginine (19) and potential substrate of pyrimidine synthesis (17,18). We demonstrated that knockdown of CPS1 induced accumulation of ammonia, a decrease of metabolites in nucleic acid synthesis pathways, and a decrease of arginine in LKB1-inactivated LADC cell lines.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…CPS1 plays a crucial role in removing excessive ammonia by converting ammonium into carbamoyl phosphate in the liver (16), which is a de novo resource of arginine (19) and potential substrate of pyrimidine synthesis (17,18). We demonstrated that knockdown of CPS1 induced accumulation of ammonia, a decrease of metabolites in nucleic acid synthesis pathways, and a decrease of arginine in LKB1-inactivated LADC cell lines.…”
Section: Discussionmentioning
confidence: 84%
“…Carbamoyl phosphate synthase 1 (CPS1) was identified as a markedly increased protein in LKB1-inactivated LADC cell lines. CPS1 is the first rate-limiting enzyme in the urea cycle, converting ammonium into carbamoyl phosphate, and plays an intricate role in arginine metabolism and pyrimidine metabolism (16)(17)(18)(19). We further investigated the effect of CPS1 through knockdown experiments and the consequences of its overexpression on survival in LADC.…”
mentioning
confidence: 99%
“…To further investigate the mechanism by which Lys 88 acetylation reduces OTC activity, we expressed (28,29), the acetylated OTC would have very low activity. It is worth noting that the K88Q mutant not only altered OTC substrate binding but also dramatically decreased the maximum velocity.…”
mentioning
confidence: 99%
“…Previous studies in laboratory animals and isolated hepatocytes treated with D-galactosamine showed that pharmacologic inhibition of ornithine carbamoyltransferase and elevation of free ammonium levels both can increase the availability of mitochondrial carbamoyl phosphate to the cytosolic compartment for synthesis of orotic acid, the precursor of pyrimidine synthesis. [57][58][59] Because D-galactosamine depletes uridine pools in liver, 60 Table 2 are shown on this simplified network. Arrows indicate the direction of reaction assumed in the model.…”
Section: Discussionmentioning
confidence: 99%